Correlation Between Non-Academic Abilities and Improvements in the Learning Achievements of Elementary School Students in Bima - Umar Umar; Retnoningsih Retnoningsih; Abdul Kadir; Mei Indra Jayanti; Angga Saputra; Muhammad Akbar (IJECA (International Journal of Education and Curriculum Application), 2026)
This study was motivated by the prevailing orientation of elementary education, which emphasizes academic achievement as the primary indicator of learning success, while non-academic dimensions such as emotional intelligence, social skills, motivation, and self-regulation have yet to receive systematic attention. In fact, the development of elementary school students requires a holistic approach to learning. This study aims to: (1) analyze the relationship between non-academic abilities and student academic achievement; (2) identify the most dominant non-academic dimensions; and (3) examine variations in relationship patterns based on school characteristics. The study employed a quantitative correlational design with an explanatory approach. The sample was selected using stratified random sampling. Data were collected using a validated Likert-scale questionnaire adapted from previous socio-emotional learning and student motivation instruments, measuring dimensions of character learning, social relationships, emotional well-being, and learning motivation, along with students’ academic grade records. The instrument was validated through expert judgment and construct validity testing. Data analysis was conducted using descriptive statistics, Pearson’s correlation, multiple linear regression, and comparative analysis across schools. The results indicate that non-academic skills have a strong and significant relationship with academic achievement (R = 0.725; R² = 0.525), contributing 52.5% of the variance. The dimension of character learning emerged as the most dominant factor, followed by learning motivation and social relationships, while emotional well-being showed a positive but statistically insignificant influence. Additionally, variations in relationship patterns were found across schools, where the dominant factors differed according to the learning environment context. These findings confirm that strengthening non-academic skills is a strategic factor in improving student academic achievement. The implications of this research encourage a transformation of teaching practices toward a more holistic, contextual, and human-centered approach, while also providing an empirical basis for the development of educational policies that strike a better balance between cognitive and non-cognitive aspects.